2011
DOI: 10.1038/modpathol.2010.217
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability and oncogene amplifications in colorectal adenomas predict recurrence and synchronous carcinoma

Abstract: Individual colorectal adenomas have different propensities to progress to invasive disease. In this study, we explored whether these differences could be explained by gene copy number alterations. We evaluated 18 adenomas of patients without synchronous or subsequent carcinoma (6.5 years follow-up), 23 adenomas of carcinoma patients, and 6 related carcinomas. All samples were measured for their DNA ploidy status. Centromere probes for chromosomes 17 and 18, as well as gene-specific probes for SMAD7, EGFR, NCOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Chromosomal instability is a well-accepted characteristic of colon cancer [27]. Similarly, DNA ploidy measurement has been established as a prognostic factor [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosomal instability is a well-accepted characteristic of colon cancer [27]. Similarly, DNA ploidy measurement has been established as a prognostic factor [28].…”
Section: Discussionmentioning
confidence: 99%
“…We feel that this is a significant observation although it is difficult to judge the frequency and importance of it due to our limited number of cases. The loss of genetic material being potentially associated with the inactivation of tumor suppressor genes may play a similarly important role in tumor progression than the activation of oncogenes [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, using conventional CGH, Ried and his colleagues described recurrent alterations in sporadic (i.e., non-hereditary) CRCs in which genomic gains affecting chromosomes 7, 8q, 13, and 20q occurred with frequencies upwards of 80 %, and genomic losses of chromosomes 4, 8p, 17p, and 18q were often observed (Ried et al 1996). In addition, several reports have shown that some of these aberrations, mainly the gain of 7 and 20q, can already be observed in preneoplastic polyps (Habermann et al 2011), and most, if not all, are still present in liver metastases of this disease and in in vitro models derived from primary tumors or metastasis (Camps et al 2009; Platzer et al 2002). The plethora of conventional and array-based CGH studies applied to map genomic imbalances in CRC convincingly confirmed these earlier results [reviewed in (Grade et al 2006a)], supporting the idea of a genomic ID associated with CRC.…”
Section: Recurrent Low-level Copy Number Alterations Among Differenmentioning
confidence: 99%
“…Interestingly, individual gene copy numbers in colorectal adenomas seem to be attributable to chromosomal aberrations by facilitating progression to carcinoma [57]. Gene-specific probes for SMAD7 (18q21.1), EGFR (7p12), NCOA3 (20q12), TP53 (17p13.1), MYC (8q24.21) and RAB20 (13q34) as well as gene-specific probes for chromosomes 17 and 18 (CEP17 and CEP18) indicated that genomic instability in colorectal adenomas is reflected by genomic amplification of the oncogenes EGFR , MYC , NCOA3 and RAB20 .…”
Section: Colon Cancer Tissue and Serum Diagnosticsmentioning
confidence: 99%